2015
DOI: 10.1101/020370
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution of ecological dominance of yeast species in high-sugar environments

Abstract: In budding yeasts, fermentation in the presence of oxygen evolved around the time of a whole genome duplication (WGD) and is thought to confer dominance in high-sugar environments because ethanol is toxic to many species. While there are many fermentative yeast species, only Saccharomyces cerevisiae consistently dominates wine fermentations. In this study, we use co-culture experiments and intrinsic growth rate assays to examine the relative fitness of non-WGD and WGD yeast species across environments to asses… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 84 publications
2
15
0
Order By: Relevance
“…In addition, during fermentation, the highest sugar consumption was observed in the sample with the highest amount (100 g/L) of added sucrose (Figure 2(a) and Table 1). This indicates that the fermentative lifestyle could exhibit a growth advantage in sugar-rich environments due to a higher rate of sugar conversion and energy production [35]. Journal of Food Quality …”
Section: Sugar Consumptionmentioning
confidence: 99%
“…In addition, during fermentation, the highest sugar consumption was observed in the sample with the highest amount (100 g/L) of added sucrose (Figure 2(a) and Table 1). This indicates that the fermentative lifestyle could exhibit a growth advantage in sugar-rich environments due to a higher rate of sugar conversion and energy production [35]. Journal of Food Quality …”
Section: Sugar Consumptionmentioning
confidence: 99%
“…A second important assumption, particularly for diversification analysis, is that taxon sampling is complete or at-least complete, and a random sample of the known diversity. This limitation is inherent to the phylogeny being used, which for the our case seems to be the most complete (studies based on Kurtzman and Robnett phylogeny: Hall et al 2005;Hagman et al 2013Hagman et al , 2014Dashko et al 2014;Hagman and Piskur 2015;Williams et al 2015). Although we don't have reasons to think that this phylogeny is biased or unrepresentative, the fact that there exist more than thousands described yeasts species (see Kurtzman et al 2011) warrants further confirmatory studies, with new, larger phylogenies.…”
Section: Discussionmentioning
confidence: 89%
“…According to a number of authors, the appearance of fruits coincided with the appareance of fermentative yeasts (especially Saccharomyces), which has supported the hypothesis of novel ecological niches provided by fruits and simple sugars (Hagman et al 2013;Dashko et al 2014;Williams et al 2015). These authors suggested that fermentative capacity represents an ecological innovation that triggered an adaptive radiation.…”
Section: Introductionmentioning
confidence: 87%
“…To measure fitness, we calculated the intrinsic growth rate (r) using the exponential growth equation (Williams et al, 2015):…”
Section: Compartmentalized Fermentationsmentioning
confidence: 99%
“…cerevisiae yeasts are characterized by their high capability to ferment simple sugars into ethanol even in the presence of oxygen, known as Crabtree effect (Crabtree, 1928). Although, alcohol fermentation is energetically much less efficient than aerobic respiration, it provides with a selective advantage to these yeasts to outcompete other microorganisms: sugar resources are consumed faster and the ethanol produced during fermentation (Goddard, 2008), as well as higher levels of heat and CO 2 , can be harmful or less tolerated by their competitors (Piskur and Langkjaer, 2004;Piškur et al, 2006;Conant and Wolfe, 2007;Merico et al, 2007;Hagman et al, 2013;Williams et al, 2015). Also, nitrogen source consumption and biomass production are more efficient in S. cerevisiae (Monteiro and Bisson, 1991;Andorrà et al, 2012).…”
Section: Introductionmentioning
confidence: 99%